Post-streptococcal reactive arthritis in children: a distinct entity from acute rheumatic fever - Barash Judith; Perl Liat; Uziel Yosef; Hashkes Philip J (BMC, 2011)
Abstract There is a debate whether post-streptococcal reactive arthritis (PSRA) is a separate entity or a condition on the spectrum of acute rheumatic fever (ARF). We believe that PSRA is a distinct entity and in this paper we review the substantial differences between PSRA and ARF. We show how the demographic, clinical, genetic and treatment characteristics of PSRA differ from ARF. We review diagnostic criteria and regression formulas that attempt to classify patients with PSRA as opposed to ARF. The important implication of these findings may relate to the issue of prophylactic antibiotics after PSRA. However, future trials will be necessary to conclusively answer that question.